Determinants of the Effectiveness of Leadership Development Programs: A Literature Review - Fazalur, Rahman; Mohmad, Yazam Sharif (2015)
In this paper, the authors will explore the determinants of the effectiveness of Leadership Development Programs (LDP) in the literature and will then develop a research framework which is suitable to be used to study the leadership phenomenon in the Oil Exploration Companies in Abu Dhabi of the United Arab Emirates (UAE). Abu Dhabi has been said to be the most influential and effective market for oil and energy related sector. The UAE government has realized the significance of oil and has invested heavily in this sector so as to achieve continuous improvement (Dhabi, 2009). In addition, Mezher et al. (2011) stated that in UAE the LDP are designed from the organizational philosophy to transform the country and organization’s strategic plan into action. Leadership can be defined as the art and science of influencing others for the achievement of organizational goals and objectives. It has become a crucial ingredient in the success and growth of organizations in the world including UAE. With this in mind, the paper also aims to highlight the importance of designing appropriate LDP so as to prepare leaders for the future. Scholars have found that there are several reasons for the effectiveness of LDP in organizations namely the ability of the programs to develop leadership skills and core competencies as well as their ability to inculcate the understanding of complexities of the business among the leaders concerned. Therefore the companies open opportunities for individuals to learn and grow more through LDP in order to make them eligible and more learned (Schein, 2010). From the literature, the authors found that leadership development has been considered by some scholars (Collins & Horton, 2004) as a critical element for an organization's long term success. The impetus for this study comes from the UAE context wherein substantial investments are being made to provide LDP to develop leadership skills of Emiratis working in the public sector, in accordance with the UAE Strategic Plan 2021 (UAE Strategic Plan, 2021). However, these programs predominantly utilize Western leadership development approaches, and tend not to consider the influence of national culture in their utilization - particularly in the selection, training, and professional development of leaders. There is extensive research on LDPs which have used different leadership theories (e.g. Day 2001, Abbas & Yaqoob 2009, Carbone 2009, Holt 2011 & Pinnington 2011). For instance, Day (2001) identified that the most popular practices to develop leaders are 360-degree feedback and executive coaching, mentoring and networking, job assignments and action learning. The 360 degree or multi-source, multi-rater (MSMR), feedback allows leaders to identify and focus on their strengths and areas for improvement. The paper will analyze critical factors that could influence the effectiveness of the LDP. This would include the external factors as well as the internal factors to the oil companies in Abu Dhabi. The development of the proposed research framework will form the basis for conducting a comprehensive study on LDP.